Generalized Anxiety disorder but not depression is associated with insomnia: a population based study - Imran Wasfi Khan; Ruchi Juyal; Deep Shikha; Ravi Gupta (Sleep Science, 2018)
Background: Insomnia is a common problem, however, its prevalence has never been examined in Indian population. Moreover, a number of psychiatric disorders have been found to be associated with insomnia in clinical population, but this association has scarcely been examined in general population. Methods: This epidemiological study was done in an urban and a rural population. Subjects were selected using Kish method. After obtaining informed consent, psychiatric disorders were diagnosed using Hindi version of Mini International Neuropsychiatric Interview. Hindi version of Insomnia Severity Index was used to diagnose insomnia. Results: 1700 subjects were included in this study. In this study, prevalence of insomnia was 10.3%. Its prevalence increased with increasing years of education (p=0.009). Insomnia was more frequent in subjects living in joint families (p<0.001), having higher education (p=0.009), those who were separated (p<0.001), among subjects belonging to middle socio-economic status (p<0.001) and in urban population compared to semi-urban and rural population (p<0.001). Insomnia was also more frequent among subjects with major depressive disorder, generalized anxiety disorder, alcohol dependence, cannabis dependence and tobacco use. However, binary logistic regression analysis showed that only higher education, unemployment, generalized anxiety disorder and tobacco use were associated with insomnia. Conclusion: Insomnia in general population is associated with higher education, unemployment, generalized anxiety disorders and tobacco use.